Animal farming and the risk of lymphohaematopoietic cancers: a meta-analysis of three cohort studies within the AGRICOH consortium. Issue 11 (13th July 2019) - El-Zaemey, Sonia; Schinasi, Leah H; Ferro, Gilles; Tual, Séverine; Lebailly, Pierre; Baldi, Isabelle; Nordby, Karl-Christian; Kjærheim, Kristina; Schüz, Joachim; Monnereau, Alain; Brouwer, Maartje; Koutros, Stella; et al.
Abstract : Objective: Animal farming entails a variety of potential exposures, including infectious agents, endotoxins and pesticides, which may play a role in the aetiology of lymphohaematopoietic cancers (LHCs). The aim of this study was to assess whether farming specific animal species is associated with the risk of overall LHC or its subtypes. Methods: Data from three prospective cohort studies in the USA, France and Norway which are part of the Agricultural Cohort consortium and which collected information about animal farming and cancer were used. Analyses included 316 270 farmers and farm workers. Adjusted Cox models were used to investigate the associations of 13 histological subtypes of LHC (n=3282) with self-reported livestock (cattle, pigs and sheep/goats) and poultry (ever/never and numbers raised) farming. Cohort-specific HRs were combined using random-effects meta-analysis. Results: Ever animal farming in general or farming specific animal species was not meta-associated with overall LHC. The risk of myeloid malignancies decreased with increasing number of livestock (p trend=0.01). Increased risk of myeloproliferative neoplasms was seen with increasing number of sheep/goats (p trend <0.01), while a decreased risk was seen with increasing number of livestock (p trend=0.02). Between cohorts, we observed heterogeneity in the association of type of animal farmed and various LHC subtypes. Conclusions: This large-scale study of three prospective agricultural cohorts showed no association between animal farming and LHC risk, but few associations between specific animal species and LHC subtypes were observed. The observed differences in associations by countries warrant further investigations.